Identification of genetic causes of congenital neurodevelopmental disorders using genome wide molecular technologies - Preikšaitienė, Eglė; Ambrozaitytė, Laima; Maldžienė, Živilė; Morkūnienė, Aušra; Cimbalistienė, Loreta; Rančelis, Tautvydas; Utkus, Algirdas; Kučinskas, Vaidutis (Acta medica Lituanica, 2016)
Background. Intellectual disability affects about 1–2% of the general population worldwide, and this is the leading socio-economic problem of health care. The evaluation of the genetic causes of intellectual disability is challenging because these conditions are genetically heterogeneous with many different genetic alterations resulting in clinically indistinguishable phenotypes. Genome wide molecular technologies are effective in a research setting for establishing the new genetic basis of a disease. We describe the first Lithuanian experience in genome-wide CNV detection and whole exome sequencing, presenting the results obtained in the research project UNIGENE.Materials and methods. The patients with developmental delay/intellectual disability have been investigated (n = 66). Diagnostic screening was performed using array-CGH technology. FISH and real time-PCR were used for the confirmation of gene-dose imbalances and investigation of parental samples. Whole exome sequencing using the next generation high throughput NGS technique was used to sequence the samples of 12 selected families.Results. 14 out of 66 patients had pathogenic copy number variants, and one patient had novel likely pathogenic aberration (microdeletion at 4p15.2). Twelve families have been processed for whole exome sequencing. Two identified sequence variants could be classified as pathogenic (in MECP2, CREBBP genes). The other families had several candidate intellectual disability gene variants that are of unclear clinical significance and must be further investigated for possible effect on the molecular pathways of intellectual disability.Conclusions. The genetic heterogeneity of intellectual disability requires genome wide approaches, including detection of chromosomal aberrations by chromosomal microarrays and whole exome sequencing capable of uncovering single gene mutations. This study demonstrates the  benefits and challenges that accompany the use of genome wide molecular technologies and provides genotype-phenotype information on 32 patients with chromosomal imbalances and ID candidate sequence variants.
Keywords: intellectual disability; developmental delay; array-CGH; whole exome sequencing